Trace and major element analysis for rock samples from Lodwar and its environs, Turkana County, Kenya - Tanui, F; Olago, D; Ouma, G; Kuria, Z (University of Oxford, 2024)
53 of 69 rock samples collected in the Lodwar region (Turkana County, Kenya) in February to June 2018 were processed and analysed to assess their chemical composition. The samples were finely ground and analysed for major elements including Na, Mg, Al, P, S, K, Ca, Fe, and Mn, as well as trace elements such as Ti, Cr, Co, Ni, Cu, Zn, As, Se, Mo, and Pb. The analytical work was conducted at the International Centre of Agriculture and Forestry (ICRAF) laboratory using X-ray diffraction (XRD) techniques. To ensure the accuracy and reliability of the results, quality control measures included meticulous sample grinding, calibration of XRD instruments, and the use of certified reference materials. This dataset provides valuable insights into the elemental composition of the rock samples, which is crucial for understanding their potential influence on groundwater quality in the region.